Fintech Ecosystem and Landscape in Russia - Soloviev, Vladimir I. (Journal of Reviews on Global Economics, 2018)
Fintech is today not only a hot mass media discussion of the future of the financial sector, but also real projects that change banking and financial services. The paper describes features and characteristics of contemporary Russian fintech landscape and ecosystem. The examples of innovative financial services in Russia, including online banking and accounting, new payments and transfers services, platforms for crowdfunding and peer-to-peer lending, blockchain initiatives, etc. are discussed. It is shown that fintech initiatives have not yet led to a radical transformation of the financial sector in Russia because participants of the fintech ecosystem have different points of view on fintech. Russian banks are now developing fintech initiatives within themselves, encouraging technology companies and fintech startups to focus their efforts on innovations that are aimed at improving processes, rather than opening new markets. The Government directs the main efforts to initiatives related to regulation of cryptocurrencies circulation and to introduction of blockchain in regtech and cybersecurity. Customers are interested in new and more convenient functionality in mobile applications, and they are waiting for new value propositions, including fast international money transfers, roboadvising, personal financial management, peer-to-peer lending.